Assessing the Effects of WFD Nutrient Reductions Within an OSPAR Frame Using Trans-boundary Nutrient Modeling - Lenhart, Hermann-Josef; Große, Fabian (Frontiers in Marine Science, 2018)
The reduction of riverine nutrients inputs is considered the means of choice to improve the eutrophication status of the southern North Sea. With the European Union's Water Framework Directive (WFD) reduction measures presently under debate, two questions arise: (1) What changes in eutrophication indicators can be expected? (2) How do the reductions by the individual member states contribute to these? We combine an element tracing method (TBNT) with a biogeochemical model to analyze the effects of WFD-compliant nitrogen reductions proposed by OSPAR's North Sea member states. We first analyze changes in selected OSPAR assessment parameters relative to a reference simulation. Second, we quantify the source-specific contributions to total nitrogen (TN) in different regions. An overall nitrogen load reduction of 14\,% is achieved. However, the response shows significant spatial variations due to strong differences between the countries' load reductions. TN and dissolved inorganic nitrogen reductions up to 60\,% and 35\,% are simulated near the Bay of Seine (France) and in the German Bight, respectively. Along the Dutch coast, reductions are below 10\,%, and no changes occur along the British coast. Reductions in chlorophyll-a are generally lower. The TBNT analysis for the German Exclusive Economic Zone shows a TN reduction in the coastal region comparable to the N reductions in the German rivers (~25\,%). In the offshore region, TN is reduced by only 6\,% due to the strong influence of riverine sources with only low reductions and non-riverine sources. Our analysis reveals that nonlinear responses in the biogeochemistry cause a faster removal of N from rivers with strong reductions by benthic denitrification, which enhances indirectly the removal of N from less reduced sources. Consequently, reductions in remote sources in non-problem areas can have a relevant positive effect on problem areas. This demonstrates that the TBNT method is an ideal tool to put in practice the ``source-oriented approach'' advocated by OSPAR, and to inform stakeholders about the effects of defined reduction strategies. However, an assessment framework is required to efficiently use it in management and for decision making, either by OSPAR, or in the context of WFD or Marine Strategy Framework Directive.